2018
DOI: 10.1016/j.neuron.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Defective Inflammatory Pathways in Never-Treated Depressed Patients Are Associated with Poor Treatment Response

Abstract: Inflammation has been involved in the pathophysiology and treatment response of major depressive disorder (MDD). Plasma cytokine profiles of 171 treatment-naive MDD patients (none of the MDD patients received an adequate trial of antidepressants or evidence-based psychotherapy) and 64 healthy controls (HCs) were obtained. MDD patients exhibited elevated concentrations of 18 anti- and proinflammatory markers and decreased concentrations of 6 cytokines. Increased inflammasome protein expression was observed in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 54 publications
8
106
0
2
Order By: Relevance
“…Together, our current findings are consistent with data on the role of immune dysfunctions in CNS diseases (Oquendo et al 2014;Wohleb et al 2016;Pantazatos et al 2017;Butovsky et al 2018), and inflammasome functional prediction of major depressive disorder treatment outcomes (Syed et al 2018). The results further lend credence to the hypothesis that neurodevelopmental and transcription-factor genes are critical mediators of complex adaptive At the systems level, the toll-like receptor (TLR) pathway genes found to be underexpressed here are documented to recognize conserved motifs in microorganisms (Akira 2003) and stimulation of TLRs are shown to mediate acute-immune defense and cytokine production/release (Perkins 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Together, our current findings are consistent with data on the role of immune dysfunctions in CNS diseases (Oquendo et al 2014;Wohleb et al 2016;Pantazatos et al 2017;Butovsky et al 2018), and inflammasome functional prediction of major depressive disorder treatment outcomes (Syed et al 2018). The results further lend credence to the hypothesis that neurodevelopmental and transcription-factor genes are critical mediators of complex adaptive At the systems level, the toll-like receptor (TLR) pathway genes found to be underexpressed here are documented to recognize conserved motifs in microorganisms (Akira 2003) and stimulation of TLRs are shown to mediate acute-immune defense and cytokine production/release (Perkins 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Third, the identified under-expressed chemokine-signaling pathways govern critical spatiotemporal cell-positioning during developmental coordination and translational guidance of cell-locomotion and migration(Turner et al 2014). Fourth, the identified under-expressed cytokines are implicated in cell-specific innate and adaptive inflammatory host defenses, cellular-development, cell-death, angiogenesis, and maintenance of cellular homeostasis(Syed et al 2018). Conversely, the Wnt-β-catenin signaling pathway found to be over-expressed in major depressive disorder suicides is an evolutionarily conserved intercellular communication system that mediates stem cell renewal, cell-proliferation and differentiation during embryogenesis and adulthood(Meffert et al 2003).…”
mentioning
confidence: 99%
“…Such results suggest that the immune system plays important roles in the onset of MDD. Both stress and inflammatory cytokine activation have been reported to have adverse effect on the neurogenesis and neural plasticity (Syed et al, 2018). By comparing our results with that of a meta-analysis on genes implicated in MDD (Gatt et al, 2015;Manoharan et al, 2016;Yin et al, 2016), we found that most of the pathways reported earlier were also identified in the current study.…”
Section: Ta B L E 1 (Continued)supporting
confidence: 68%
“…Interleukin-17 in the IL-17 signaling pathway plays a crucial role in acute and chronic inflammatory responses (Zhao, Li, Li, Wang, Manthari, & Wang, 2018). Both stress and inflammatory cytokine activation have been reported to have adverse effect on the neurogenesis and neural plasticity (Syed et al, 2018). Such results suggest that the immune system plays important roles in the onset of MDD.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Cytokines generated in these responses regulate cell-mediated immunity and phagocytic-dependent inflammation in response to intracellular parasites and can promote autoimmunity (Calcagni & Elenkov, 2006). While the variance in the magnitude and types of overexpressed cytokines can be significant between trials and results can conflict (Orlovska-Waast et al, 2018), a set of cytokines including IL-1β, TNF-α, IL-6, IL-18, IL-17A, and IL-10 do exhibit consistent up regulation in the plasma of untreated MDD patients (Hodes, Kana, Menard, Merad, & Russo, 2015;Syed et al, 2018). Similar alterations in the concentration of these cytokines are noted in their CSF (Young, Bruno, & Pomara, 2014).…”
Section: Shared Cytokines and Chemokine Profilementioning
confidence: 99%